ANALISIS PENGARUH MEREK, KUALITAS DAN HARGA PRODUK MOTOR HONDA "VARIO CBS TECHNO" DENGAN KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada PT ASTRA MOTOR PATI) - Dody Wijaya__, 09.05.51.0116; Hersugondo, Hersugondo (Students Journal of Economic and Management, 2012)
Thepurpose of this research is to examine and analyze the influence of the brand, quality and price on purchase decisions Honda "VARIO CBS TECHNO". The sample used in this study were 100 respondents who bought a Honda purchase "VARIO CBS TECHNO" accidental sampling method is a sample taken from anyone who happened to be there. collecting the data used in this research is using questionnaires (questionnaire) by spreading a list of questions to respondents in order to obtain information. Data collected performed using analysis Factor Test Validity, Test Relibilitas using Cronbach alpha formula, Test Multiple Regression, Coefficient of Determination Test conducted to determine the influence of Variable penelitianan, F test and t-test. The results of the study are: (1) brand has positive and significant impact on purchasing decisions (2) Quality has positive and significant impact on purchasing decisions (3) for a positive and significant impact on purchasing decisions (4) jointly branded, quality and price influence on purchasing decisions. The results of statistical calculation by linear regression analysis it can be concluded that the price has a great influence on the purchase decision and then the brand and quality of the product. (5) The calculation of the coefficient of determination R-square value of 0568 or 56.8%. Thus it can be said that purchasing decisions are influenced by brand, quality and price by 56.8%, while 43.2 influenced by other variables that are not included in this study.Key words: - Brand, Quality, Price, Purchase Decision